Back to the future of the Arctic: The enduring relevance of arms control - Michael Paul (Stiftung Wissenschaft und Politik (SWP), 2024)
Russia's war against Ukraine seems to have no immediate end in sight, the strategic competition between China and the US continues, and the expanding military cooperation between China and Russia increases the challenges facing the international community. In this context, the Arctic seems to be a relic of the past, no longer the "zone of peace" that Mikhail Gorbachev described in 1987. Indeed, this Arctic exceptionalism ended long before Russia's war of aggression began. In order to restore at least a minimum level of cooperation, informal talks are needed that could help to provide perspective after the end of the war. Two former relatively uncontroversial projects could serve as starting points: the recovery of radioactive remnants of the Cold War and an agreement to prevent unintentional escalation, namely, another Incidents at Sea Agreement (INCSEA). A return to old approaches to arms control could pave the way to renewed cooperation in the Arctic in the future.
Keywords: 320; Arctic; Arms Control; Russia's war against Ukraine; zone of peace; Vladimir Putin; Arctic Zone of the Russian Federation (AZRF); NATO; Arctic Council; Incidents at Sea Agreement (INCSEA); Arctic Security Forces Roundtable (ASFR)